2003
DOI: 10.1097/01.lab.0000101728.93907.75
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Placental Leucine Aminopeptidase and Adipocyte-Derived Leucine Aminopeptidase in Human Normal and Malignant Invasive Trophoblastic Cells

Abstract: SUMMARY:We recently identified two novel aminopeptidases, placental leucine aminopeptidase (P-LAP) and adipocytederived leucine aminopeptidase (A-LAP). Enzymatically, P-LAP degrades oxytocin, vasopressin, and angiotensin III, while A-LAP degrades angiotensin II and kallidin. In this study we investigated the expression and localization of P-LAP and A-LAP in human trophoblastic cells in the normal placenta (n ϭ 26), gestational choriocarcinoma (n ϭ 8), and placental site trophoblastic tumor (n ϭ 3). On immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Because of the resistance of glioma cells to conventional therapies, it is very difficult to cure; however, the identification of genes or proteins that effectively promote or inhibit tumor growth, migration and invasion is imperative [25]. The dysregulation expression of LAPs (leucine aminopeptidases) could result in changes in tumor cell proliferation, invasion and/or angiogenesis, such as endometrial carcinoma, endothelial cells, breast cancer, trophoblastic neoplasms, ovarian cancer [11][12][13][14][15]. But the study of LAP3 in neoplasms is less, the latest research reported LAP3 is upregulateed in human esophageal squamous cell carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the resistance of glioma cells to conventional therapies, it is very difficult to cure; however, the identification of genes or proteins that effectively promote or inhibit tumor growth, migration and invasion is imperative [25]. The dysregulation expression of LAPs (leucine aminopeptidases) could result in changes in tumor cell proliferation, invasion and/or angiogenesis, such as endometrial carcinoma, endothelial cells, breast cancer, trophoblastic neoplasms, ovarian cancer [11][12][13][14][15]. But the study of LAP3 in neoplasms is less, the latest research reported LAP3 is upregulateed in human esophageal squamous cell carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addtion, P-LAP also promotes the progression of breast cancer [14]. P-LAP and A-LAP were predominantly expressed in the invasive phenotype of EVTs during placentation, as well as in the invasive tumor cells of trophoblastic neoplasms [15]. PT-PCR and Western blot showed that the expression of LAP3 was increased in high-grade glioma tissues (grade III and grade IV) compared with in low-grade glioma tissues (grade II) and in normal brain.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatically, aminopeptidases hydrolyze N-terminal amino acids of peptide substrates with their own specificity. Recently, our group identified A-LAP in human invasive trophoblastic cells (Ino et al 2003). Among the bioactive peptides, it appears that angiotensin II may play important roles in such processes as angiogenesis, vasoconstriction, and trophoblast invasion in the cyclic endometrium (Li and Ahmed 1996;Ando et al 2002;Xia et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin (3-8) (Ang IV) has been shown to influence blood flow through a mechanism mediated by its specific receptor (AT4 receptor) and nitric oxide. Ino et al [41] have previously described AT4 receptors in extravillous trophoblasts and suggested they may play a role in placentation. AT4 receptors are known to be upregulated in healthy placentae, possibly as a control mechanism to prevent Ang IV binding to the AT1 receptor.…”
Section: Pathophysiology Of Pre-eclampsiamentioning
confidence: 98%